T&T Clark reader in abortion and religion Jewish, Christian, and Muslim perspectives - Peters, Rebecca Todd 1967-; Kamitsuka, Margaret D. (London New York Oxford New Delhi Sydney t&tclark, 2023)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Credit Lines -- Contents -- Author Information -- Acknowledgments -- A Note from the Editors -- Introduction -- Part I: In Their Own Words -- Introduction to Part 1 -- Chapter 1: So Many Lives at Stake -- Chapter 2: In the Shade of Allah's Mercy -- Chapter 3: Reproducing Justice -- Chapter 4: Christ Was There for Me during My Abortion -- Chapter 5: Lo Teivoshi, You Will Not Feel Ashamed -- Chapter 6: You're the Only One I've Told -- Part II: Social-Scientific Studies -- Introduction to Part 2 -- Chapter 7: Understanding Why Women Seek Abortions in the United States -- Chapter 8: "I'm Not That Type of Person":: Managing the Stigma of Having an Abortion -- Chapter 9: Women's Decision Making Regarding Choice of Second Trimester Termination Method for Pregnancy Complications -- Chapter 10: Muslim Women Having Abortions in Canada:: Attitudes, Beliefs, and Experiences -- Chapter 11: Ultra-Orthodox Jewish Women Navigating the Uncertainty of Pregnancy and Prenatal Diagnosis -- Chapter 12: The State of Abortion and Contraception Attitudes in All 50 States -- Chapter 13: Faith, Race-Ethnicity, and Public Policy Preferences:: Religious Schemas and Abortion Attitudes among US Latinos -- Chapter 14: Ethnic Diversity, Religion, and Opinions toward Legalizing Abortion:: The Case of Asian Americans -- Part III: History and Context -- Introduction to Part 3 -- Chapter 15: Undesired Offspring and Child Endangerment in Jewish Antiquity -- Chapter 16: Selected Early Catholic Teaching on Abortion -- Chapter 17: Imagining Abortivi in the Early Middle Ages -- Chapter 18: Pre-modern Islamic Medical Ethics and Graeco-Islamic-Jewish Embryology -- Chapter 19: Abortion and Law in the High Middle Ages -- Chapter 20: Contraception in Protestant Theology:: A Brief and Incomplete History.
Description based on publisher supplied metadata and other sources
Keywords: Abortion-Religious aspects-Christianity; Abortion -- Religious aspects -- Christianity; Abortion -- Religious aspects -- Judaism; Abortion -- Religious aspects -- Islam; Electronic books